2007
DOI: 10.1038/sj.eye.6702751
|View full text |Cite
|
Sign up to set email alerts
|

Protein carbonyl levels in the aqueous humour and serum of patients with pseudoexfoliation syndrome

Abstract: Purpose Protein oxidation is an oxidative stress marker and the oxidation of proteins is analysed by measuring the carbonyl groups. Protein oxidation can have a role in the physiopathology of pseudoexfoliation (PEX) syndrome. The aim of this study was to investigate the protein oxidation in the aqueous humour and serum of cataract patients with and without PEX. Methods A multicenter study was carried out. Aqueous humour and serum samples were collected from patients who underwent routine cataract surgery. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The current study, which included 202 subjects with OAG, is the largest such study to assess the systemic redox status in glaucoma 15 17 18 19 20 21 22 23 24 25 26 27 28 29 . Yagci et al .…”
Section: Discussionmentioning
confidence: 99%
“…The current study, which included 202 subjects with OAG, is the largest such study to assess the systemic redox status in glaucoma 15 17 18 19 20 21 22 23 24 25 26 27 28 29 . Yagci et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported lower systemic levels of antioxidants or antioxidative stress capacity in glaucoma [ 15 , 18 , 20 , 21 , 23 , 28 ]. Other studies have tested simultaneously the status of systemic and local redox [ 16 , 17 , 22 , 24 ]. Yagci et al found increased protein carbonylation, which is a measure of protein oxidation, in aqueous and serum samples from EX compared with controls [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have tested simultaneously the status of systemic and local redox [ 16 , 17 , 22 , 24 ]. Yagci et al found increased protein carbonylation, which is a measure of protein oxidation, in aqueous and serum samples from EX compared with controls [ 16 ]. Koliakos et al identified significantly lower levels of antioxidative stress enzyme catalase activities in aqueous and serum samples from EX compared with controls [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eye is an exceptional organ because of its continuous exposure to environmental chemicals, radiation, and atmospheric oxygen. Oxidative stress mechanisms in ocular tissues have been hypothesized to play a role in diseases such as cataracts, glaucoma, uveitis, pseudoexfoliation syndrome, and age-related macular degeneration [16,17]. …”
Section: Introductionmentioning
confidence: 99%